Fulminant Hepatic Failure as the Initial Presentation of Hodgkin's Disease and Liver Transplantation: A Case Report - Mauricio Alejandro Saldaña Ruiz; Federico Ortiz-Alonso; Adriana Carolina Sandoval-González; Liliana Sayuri Tapia-Brito; Laura Carolina Lozano-Galván; Karla Monserrat Ramírez-Pintor (University Library System, University of Pittsburgh, 2024)
Background: Hodgkin's disease, a B-cell neoplasm, primarily impacts lymph nodes or extranodal lymphoid tissue. It includes two distinct entities: classical (95%) and lymphocyte-predominant nodular. While the disease commonly manifests as the growth of cervical and intrathoracic lymph nodes in 60-90% of cases, there are rare instances where Hodgkin's disease has been linked to fulminant liver failure, carrying a very poor prognosis. The Case: We present the case of a 13-year-old Hispanic female, who started with an insidious condition that evolved to fulminant hepatic failure of unknown etiology with an AST of 770 mg/dl. It was decided to perform an orthotopic liver transplant, the histopathological analysis of the explant and a lymph node reported mixed cellularity Hodgkin's disease. Subsequently, the hematology service requested a lumbar puncture, with no evidence of infiltration. It was decided to initiate six cycles of chemotherapy (CTX) with BEACOPP (bleomycin, etoposide, adriamycine, cyclophosphamide, vincristine, procarbazine, and prednisone) scheme, evolving without complications and achieving a complete response eleven months later; currently, she has been free of disease for three years. Conclusion: The etiology of Hodgkin's disease in our 13-year-old patient remains elusive, emphasizing the importance of early diagnosis and diverse treatment approaches. Despite limited hospital resources, the decision to proceed with the transplant was driven by the potentially fatal outcome if left untreated. Future considerations may necessitate individualizing each case, and carefully assessing the risks and benefits associated with transplantation.